New report from presence and distribution of Allactaga firouzi in Iran - Saeed Mohammadi; Gholamreza Naderi (African Journal of Environmental Economics and Management, 2022)
The Iranian jerboa Allactaga firouzi (Womochel, 1978) is one of the rarest rodent species in the world and it has been reported exclusively from a single site in central Iran. Due to the lack of enough information on the ecology of this species, its conservation status was changed to “Data Deficient” category in late 2008. No additional data on A. firouzi was published since its first description by Womochel. Here we report the results of recent intensive survey work in south of Shah-Reza city that yielded several new localities for this species. New localities of A. firouzi were identified.